River road [compact disc, unabridged] - Krentz, Jayne Ann (Recorded Books, 2014)
It's been thirteen years since Lucy was in Summer River. The last time she visited her aunt Sara, as a teenager, she was sent home after being dragged out of a party by the boy she had a crush on - Mason Fletcher. Returning after her aunt's death, Lucy is learning there was more to the story. A lot has changed, but when Mason and Lucy make a shocking discovery inside Sara's house, his quietly fierce instincts kick into gear. But this time, she insists on playing a role in her own rescue.